2006
DOI: 10.1196/annals.1377.019
|View full text |Cite
|
Sign up to set email alerts
|

FAK Signaling in Neoplastic Disorders

Abstract: Focal adhesion kinase (FAK), a nonreceptor protein tyrosine kinase, is frequently overexpressed in various tumors and its expression shows good correlation with the progression of tumor. FAK is involved in a diverse range of critical cellular events including spreading, proliferation, migration, and invasion. In addition to these cellular functions, we found that FAK signaling played a critical role in the production of matrix metalloproteinases (MMP) such as MMP-2 and MMP-9 and subsequently activated tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 79 publications
1
44
0
1
Order By: Relevance
“…We also show here that MMP-2 is able to promote cell invasion in SCC cells. Previous studies have supported a role for FAK in MMP-2 secretion in response to environmental factors (Sein et al, 2000;Zhang et al, 2002;Mon et al, 2006b). Our studies show that FAK is implicated in MMP-2 gene expression leading to increased MMP-2 secretion in SCC cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also show here that MMP-2 is able to promote cell invasion in SCC cells. Previous studies have supported a role for FAK in MMP-2 secretion in response to environmental factors (Sein et al, 2000;Zhang et al, 2002;Mon et al, 2006b). Our studies show that FAK is implicated in MMP-2 gene expression leading to increased MMP-2 secretion in SCC cells.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, transient overexpression of FAK in SCC cells increases cell invasion. Several reports have shown that FAK can regulate cell invasion not only by regulation of cell migration but also by the modulation of matrix metalloproteinases that degrade extracellular matrix barriers (Hsia et al, 2003;Mon et al, 2006b). We found that MMP-2 and MMP-9 gene expression were greatly reduced by FRNK expression in SCC40 cells.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have indicated that Src and FAK are related to cancer progression and invasion (32)(33)(34). Elevated Src expression has been observed in different types of cancer, including colon, breast, pancreatic and gastric cancer (27).…”
Section: A B C Dmentioning
confidence: 99%
“…Pro-MMPs lie dormant within the ECM and are activated by various signals (Murphy et al, 1999;Davidson et al, 2002;Tsuruda et al, 2004;Nagase et al, 2006;Amalinei et al, 2007;Ra and 2008). Misregulation of MMP activity contributes to multiple diseases (metastatic carcinoma, cardiovascular disease, rheumatoid arthritis, osteoarthritis, oral diseases) and is also implicated in preterm labor (Davidson et al, 2002;Abraham et al, 2005;Hofmann et al, 2005;Vadillo-Ortega and Estrada-Gutierrez, 2005;Lemaitre and D'Armiento, 2006;Liu et al, 2006;Mon et al, 2006;Cockle et al, 2007). The dynamic interaction between ECM synthesis/ assembly and degradation via MMPs is an exquisite balancing act that mediates both embryonic development and tissue homeostasis.…”
Section: Extracellular Matrix Proteinsmentioning
confidence: 99%